Foliar application effect of gibberellic acid on growth, yield components and some qualitative characteristics of linseed (Linium usitatissimum L.) - Bahar Jalal Mahmood; Kazhal Kamal Muhammad (Zanco Journal of Pure and Applied Sciences, 2022)
The highest values (22.16, 18.63, 0.44, 5.58 and 7.25) % for oleic, linoleic, linolenic, palmitic and stearic acid respectively which were recorded from the interaction treatment of GA3 (375 mg L-1) x Syrian Cultivar. Strong positive correlation was found between seed yield to each of (plant height (cm), fruiting stem (cm), number of branch plant-1, stem width (mm), number of capsule plant-1, number seed capsule-1, seed index (g), harvest index %, oil yield (Mg ha-1) with the correlation coefficient(r) values of (0.87**,0.86**,0.89**.0.81**,0.79**,0.77**,0.98** ,0.96**and 0.99**.